Evaluation of the subjective efficacy of nasal surgery. Issue 1 (5th December 2016) - Wu, J; Zang, H R; Wang, T; Zhou, B; Ye, J Y; Li, Y C; Han, D M
Abstract: Objectives: This study aimed to evaluate subjective symptom changes in obstructive sleep apnoea hypopnea syndrome patients following nasal surgery, and to explore treatment efficacy in improving patient quality of life. Methods: Patients with nasal blockage accompanied by habitual snoring were stratified into four groups. Their subjective symptoms were evaluated before and after nasal surgery. Results: There was a significant decrease in the nasal blockage symptom visual analogue scale, Epworth Sleepiness Scale, Snore Outcomes Survey, Spouse/Bed Partners Survey and Sino-Nasal Outcome Test 20 scores for all patients at six months after surgery. The visual analogue scale score for subjective olfactory function was significantly improved in the severe obstructive sleep apnoea hypopnea syndrome patient group. Conclusion: Nasal surgery can effectively improve the subjective symptoms of patients with simple snoring accompanied by nasal blockage and of patients with obstructive sleep apnoea hypopnea syndrome, thus improving their quality of life.